ANALYZING THE EFFECT OF EVOLUTIONARY REBRANDING TOWARD FANS LOYALTY AND REPURCHASE INTENTION: CASE STUDY OF JUVENTUS FOOTBALL CLUB LOGO CHANGE - Muharrama, Rivadi Ariq; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract. Nowadays, many brands are modifying their brand element, or better known as evolutionary rebranding. In January 2017, Juventus Football Club, decided to replace their old logo with a new logo that came into use on July 1, 2017. No matter how good the approach to their fans, evolutionary rebranding will surely produce two results, which is either successful or failed. The failure might be due to not all fans will agree with the decision taken by the brand, in this case, by Juventus FC. Because the object of the research is a football club, then the customer referred here is the fans of Juventus itself. The results of this study find out how evolutionary rebranding affect fans loyalty and how fans loyalty affect fans repurchase intention. Also this study discusses about the relationship between fans satisfaction, brand attitude and fans loyalty. A quantitative approach is applied by spreading online questionnaire to Juventus fans and collecting 286 responses. The results will be assessed using structural equation modelling. The findings revealed that all factors that relate with fans loyalty and repurchase intention, direct or indirect have significant effect with one another. Moreover, Juventus evolutionary rebranding positively and significantly has effect on fans loyalty indirectly.Keywords: Evolutionary Rebranding, Fans Loyalty, Repurchase Intention, Juventus FC.